2021
DOI: 10.2166/wst.2021.210
|View full text |Cite
|
Sign up to set email alerts
|

Study on anti-scaling of landfill leachate treated by evaporation method

Abstract: In the mechanical vapor recompression (MVR) treatment of landfill leachate, scaling in the evaporator and heat exchanger poses a serious problem. This study explored the reasons for such scaling and proposed acid or ion-exchange pre-treatments to reduce the alkalinity of the landfill leachate nanofiltration concentrate (LLNC) to prevent scaling. The feasibility of these two methods was evaluated and the technical and economic parameters for application were obtained via experiments. A large amount of HCO3- in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
(28 reference statements)
0
0
0
Order By: Relevance
“…[48] Scaling prevention by reducing the alkalinity of the landfill leachate nanofiltration concentration (LLNC). Ion exchange pre-treatment revealed that a moderately acidic cation-exchange resin outperformed a strongly acidic cation-exchange resin [49]. Compared to the raw LLNC up to 92.9%, the solid residue declined at alkalinity 0 mg/l.…”
Section: Ion Exchange Processmentioning
confidence: 97%
“…[48] Scaling prevention by reducing the alkalinity of the landfill leachate nanofiltration concentration (LLNC). Ion exchange pre-treatment revealed that a moderately acidic cation-exchange resin outperformed a strongly acidic cation-exchange resin [49]. Compared to the raw LLNC up to 92.9%, the solid residue declined at alkalinity 0 mg/l.…”
Section: Ion Exchange Processmentioning
confidence: 97%